Association between dietary flavonoid intake and hypertension among U.S. adults - Wan, Yingying; Ma, Dan; Shang, Qinghua; Xu, Hao (Frontiers in Immunology, 2024)
Hypertension is one of the major risk factors for cardiovascular disease. Dietary flavonoids have been reported to reduce inflammation, protect against oxidative stress, protect the vascular endothelium, and improve vascular health. However, the relationship between dietary flavonoid intake and the prevalence of hypertension remains controversial.This study included 8010 adults from the 2007-2010 and 2017-2018 National Health and Nutrition Examination Surveys (NHANES). The relationship between dietary flavonoid intake and the prevalence of hypertension was explored by weighted logistic regression and weighted restricted cubic spline.We found an inverse relationship between total anthocyanin intake and the prevalence of hypertension in the fourth quartile compared with the first quartile [0.81(0.66,0.99), p = 0.04]. Moreover, the prevalence of hypertension tended to decrease with increasing total anthocyanin intake in participants over 60 years of age. In addition, we found a U-shaped relationship between the prevalence of hypertension and total flavan-3-ol intake. Total flavan-3-ol intake was inversely associated with hypertension prevalence in the third quartile compared with the first quartile [0.79 (0.63,0.99), p = 0.04]. Moreover, there was a significant negative association between the prevalence of hypertension and total flavan-3-ol intake when total flavan-3-ol intake was below 48.26 mg/day.Our study found a negative association between the prevalence of hypertension and moderate total anthocyanins intake and total flavan-3-ols intake. Our study provides evidence from a population-based study for a negative association between dietary flavonoid intake and